2021
DOI: 10.1371/journal.pone.0248348
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a well-characterized SARS-CoV-2 lentiviral pseudovirus neutralization assay using 293T cells with stable expression of ACE2 and TMPRSS2

Abstract: Pseudoviruses are useful surrogates for highly pathogenic viruses because of their safety, genetic stability, and scalability for screening assays. Many different pseudovirus platforms exist, each with different advantages and limitations. Here we report our efforts to optimize and characterize an HIV-based lentiviral pseudovirus assay for screening neutralizing antibodies for SARS-CoV-2 using a stable 293T cell line expressing human angiotensin converting enzyme 2 (ACE2) and transmembrane serine protease 2 (T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(172 citation statements)
references
References 63 publications
9
160
2
1
Order By: Relevance
“…Numerous studies have demonstrated that the spike protein may be employed to generate stably pseudotyped lentiviral, retroviral, and vesicular stomatitis virus particles (Crawford et al, 2020;Johnson et al, 2020;Plescia et al, 2020;Shang et al, 2020;Neerukonda et al, 2021). Given that live SARS CoV-2 is a biosafety level-3 agent, these pseudotyping approaches have greatly facilitated investigations undertaken within lower containment facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the spike protein may be employed to generate stably pseudotyped lentiviral, retroviral, and vesicular stomatitis virus particles (Crawford et al, 2020;Johnson et al, 2020;Plescia et al, 2020;Shang et al, 2020;Neerukonda et al, 2021). Given that live SARS CoV-2 is a biosafety level-3 agent, these pseudotyping approaches have greatly facilitated investigations undertaken within lower containment facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Proof of principle for this has been demonstrated with a HIV-based lentiviral pseudovirus assay in a HEK 293T cell line expressing human ACE2 and TMPRSS2 (Neerukonda et al, 2021). This assay has shown success in screening for neutralizing antibodies for SARS-CoV-2 (Neerukonda et al, 2021).…”
Section: Human In Vitro Modelsmentioning
confidence: 99%
“…Codon optimized full-length open reading frames of the S genes of SARS-COV2 variants were cloned into pCDNA3.1(+) by GenScript (Piscataway, NJ). 293T-ACE2.TMPRSS2s cells stably expressing human angiotensin converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) were established as previously described (8). The 293T and 293T-ACE2.TMPRSS2s cells were maintained at 37°C in Dulbecco's modified eagle medium (DMEM) supplemented with high glucose, L-Glutamine, minimal essential media (MEM) non-essential amino acids, penicillin/streptomycin and 10% fetal bovine serum (FBS).…”
Section: Plasmids and Cell Linesmentioning
confidence: 99%
“…These studies were performed as part of a package of standardized assays established by the U.S. government's COVID-19 Therapeutics response efforts. The assays utilized product samples provided by the manufacturers, and the results were blinded to the products tested and published (8)(9). Multiple therapeutic products did not retain the ability to neutralize multiple variants including the Alpha, Beta and Gamma variants that were previously supplanting other earlier SARS-2 variants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation